Exploring Motivation and Resilience Among Badminton Players: A Correlational Study (Journal of Asian Development Studies, 2025)
This study aimed to explore the impact of intrinsic and extrinsic motivation, as well as perceived stress, on athlete resilience. A cross-sectional study was conducted with 250 badminton players (18–37 years) in Pakistan, using self-report questionnaires to assess motivation profiles (SMS-6), perceived stress (PSS-10), and resilience (Athlete Resilience Checklist; ARC). The analysis revealed that athletes exhibited a relatively high level of resilience (M = 85.89) and a moderate level of perceived stress (M = 31.99). Intrinsic motivation showed a positive but non-significant correlation with resilience, while extrinsic motivation, particularly external regulation (r = 0.345, p < 0.01), demonstrated a significant positive association. Identified regulation had a significant negative correlation with resilience (r = -0.228, p = 0.047), and motivation showed a significant negative correlation (r = -0.257, p < 0.001). Interestingly, the "lack of self-efficacy" subcomponent of perceived stress exhibited a significant positive correlation with resilience (r = 0.454, p < 0.001). These findings suggest that perceived stress, particularly related to self-efficacy, plays a significant role in shaping resilience among athletes.